SIRPα Mismatch Is Associated With Relapse Protection and Chronic Graft-Versus-Host Disease After Related Hematopoietic Stem Cell Transplantation for Lymphoid Malignancies - Saliba, Rima M.; Srour, Samer A.; Greenbaum, Uri; Ma, Qing; Carmazzi, Yudith; Moller, Michael; Wood, Janet; Ciurea, Stefan O.; Kongtim, Piyanuch; Rondon, Gabriela; Li, Dan; Saengboon, Supawee; et al. (Frontiers in Immunology, 2022)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potentially curative therapy for hematologic malignancies. Alloreactivity after HSCT is known to be mediated by adaptive immune cells expressing rearranging receptors. Recent studies demonstrated that the innate immune system could likewise sense the non-self signals and subsequently enhance the alloimmune response. We recently demonstrated that the donor/recipient mismatch of signal regulatory protein α (SIRPα), an immunoglobulin receptor exclusively expressed on innate cells, is associated with a higher risk of cGVHD and relapse protection in a cohort of acute myeloid leukemia patients who underwent allo-HSCT. Whether these effects also occur in other hematologic malignancies remains unclear. In the present study, we compared outcomes by SIRPα match status in a cohort of 310 patients who received allo-HSCT from an HLA matched-related donor for the treatment of lymphoid malignancies. Multivariable analysis showed that SIRPα mismatch was associated with a significantly higher rate of cGVHD (hazard ratio [HR] 1.8, P= .002), cGVHD requiring systemic immunosuppressive therapy (HR 1.9, P= .005), a lower rate of disease progression (HR 0.5, P= .003) and improved progression-free survival (HR 0.5, P= .001). Notably, the effects of SIRPα mismatch were observed only in the patients who achieved >95% of donor T-cell chimerism. The mismatch in SIRPα is associated with favorable relapse protection and concurrently increased risk of cGVHD in patients who undergo allo-HSCT for lymphoid malignancies, and the optimal donor could be selected based on the finding of the study to mitigate the risk of GVHD and relapse.